Intravenous heroin-associated delayed spongiform leukoencephalopathy: Case report and reviews of the literature - Pattarin Pirompanich (2018)
© 2015, Medical Association of Thailand. All rights reserved. Heroin-associated spongiform leukoencephalopathy is a rare, and sometimes fatal, condition usually caused by vapor inhalation of heroin. The authors report a 41-year-old man who was diagnosed with delayed spongiform leukoencephalopathy three weeks after injecting heroin intravenously. He had been admitted to another hospital due to acute heroin overdose, which had occurred four hours after intravenous injection of an unknown amount of heroin. His clinical condition showed progressive improvement and he was discharged 12 days after admission. Three weeks after this episode, his cognitive functioning declined. Akinetic mutism, spasticity and hyperreflexia of all extremities were observed. Electroencephalography (EEG) and imaging of the brain showed typical characteristics of spongiform leukoencephalopathy. The three and six-month follow-up of the patient showed clinical improvement and this was corroborated through EEG measures and brain imaging. The discussion summarizes eight previously reported cases of intravenous heroin associated spongiform leukoencephalopathy and compares them to the authors’ case.